2012
DOI: 10.7314/apjcp.2012.13.12.6155
|View full text |Cite
|
Sign up to set email alerts
|

Common Docking Domain Mutation E322K of the ERK2 Gene is Infrequent in Oral Squamous Cell Carcinomas

Abstract: Background: Mutations in the MAPK (Mitogen Activated Protein Kinase) signaling pathway -EGFR/Ras/ RAF/MEK have been associated with the development of several carcinomas. ERK2, a downstream target of the MAPK pathway and a founding member of the MAPK family is activated by cellular signals emanating at the cell membrane. Activated ERK2 translocates into the nucleus to transactivate genes that promote cell proliferation. MKP -a dual specific phosphatase -interacts with activated ERK2 via the common docking (CD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…MAPK1 codes for ERK2, a mitogen-activated signaling (MAPK) pathway member downstream of Raf and MEK (Figure 2C), and the E322 locus is highly conserved across species (Figure 2D). 27 The E322K mutation occurs in approximately 1% of HNSCC 28,29 and 8% of cervical squamous cell carcinomas. 30 MAPK1 E322K causes constitutive activation of ERK2.…”
Section: Resultsmentioning
confidence: 99%
“…MAPK1 codes for ERK2, a mitogen-activated signaling (MAPK) pathway member downstream of Raf and MEK (Figure 2C), and the E322 locus is highly conserved across species (Figure 2D). 27 The E322K mutation occurs in approximately 1% of HNSCC 28,29 and 8% of cervical squamous cell carcinomas. 30 MAPK1 E322K causes constitutive activation of ERK2.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to Raf and MEK, extracellular signal-regulated kinase (ERK, also known as mitogen-activated protein kinase; MAPK) has been reported to have over 100 downstream cytoplasmic and nuclear targets, including transcription factors that drive the expression of D-type cyclins which initiate the cell cycle [36,72]. Whilst overexpression of ERK has been reported in OSCC [5,73], the reported incidence of this is low compared to mutations in the RAS gene [74]. Interestingly, in silico pathway analysis found that both ERK/MAPK and RAS (along with AKT and mTOR) expression levels were substantially lower in pre-cancerous OLK compared to OSCC, resulting in speculation that mutation in these particular genes results in acquisition of the cancer phenotype [5].…”
Section: Ras-raf-mek-erk/mapk Pathwaymentioning
confidence: 99%
“…MAPK1 encodes ERK2, which will be referred to as MAPK1, a component of the mitogen activated signaling (MAPK) pathway downstream of RAS, RAF and MEK. The MAPK1 E322K hotspot mutation, which causes constitutive activation of ERK2 [ 7 , 8 ], occurs in approximate 1.3% of HNSCC [ 9 , 10 ] and in 8% of cervical squamous cell carcinomas [ 11 ].…”
Section: Introductionmentioning
confidence: 99%